2013
DOI: 10.1017/s0031182013000802
|View full text |Cite
|
Sign up to set email alerts
|

Current status of the genetics and molecular taxonomy ofEchinococcusspecies

Abstract: The taxonomy of Echinococcus has long been controversial. Based mainly on differences in morphology and host-parasite specificity characteristics, 16 species and 13 subspecies were originally described. Subsequently, most of these taxa were regarded as synonyms for Echinococcus granulosus and only 4 valid species were recognised: E. granulosus; E. multilocularis; E. oligarthrus and E. vogeli. But, over the past 50 years, laboratory and field observations have revealed considerable phenotypic variability betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 48 publications
0
43
0
7
Order By: Relevance
“…Around one million or more people are currently suffering from CE globally and the financial burden of the disease on the livestock industry is substantial, with up to two billion dollars lost annually [1]. Recent molecular phylogenetic analyses have revealed that E. granulosus is a complex of spesies/genotypes with at least five different species: E. granulosus sensu stricto (s.s.) (genotypes G1-G3), Echinococcus equinus (G4), Echinococcus ortleppi (G5), Echinococcus canadensis (G6-G10), and Echinococcus felidis ("lion strain") [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around one million or more people are currently suffering from CE globally and the financial burden of the disease on the livestock industry is substantial, with up to two billion dollars lost annually [1]. Recent molecular phylogenetic analyses have revealed that E. granulosus is a complex of spesies/genotypes with at least five different species: E. granulosus sensu stricto (s.s.) (genotypes G1-G3), Echinococcus equinus (G4), Echinococcus ortleppi (G5), Echinococcus canadensis (G6-G10), and Echinococcus felidis ("lion strain") [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Around one million or more people are currently suffering from CE globally and the financial burden of the disease on the livestock industry is substantial, with up to two billion dollars lost annually [1]. Recent molecular phylogenetic analyses have revealed that E. granulosus is a complex of spesies/genotypes with at least five different species: E. granulosus sensu stricto (s.s.) (genotypes G1-G3), Echinococcus equinus (G4), Echinococcus ortleppi (G5), Echinococcus canadensis (G6-G10), and Echinococcus felidis ("lion strain") [2][3][4].CE remains one of the most important helminth zoonoses in many regions of Europe, especially the Mediterranean littoral (Spain, Italy, Greece and Turkey) and southeastern countries such as Bulgaria and Romania. The disease seems to be less prevalent in the UK, Central Europe, the Baltic States and the Scandinavian countries [5,6].…”
mentioning
confidence: 99%
“…During recent decades, based on mitochondrial and nuclear genetic markers, a number of variants have been described within the E. granulosus species. 17 These strains/genotypes vary in host range, pathogenicity, maturation patterns of the parasite, epidemiology and sensitivity to chemotherapeutic agents, and prevention and control strategies of hydatid disease. 18 To date, 10 genotypes (G1-G10) have been identified for E. granulosus.…”
Section: Introductionmentioning
confidence: 99%
“…These genotypes consist of two sheep strains (G1 and G2), two bovid strains (G3 and G5), a horse strain (G4), a camel strain (G6), two pig strains (G7 and G9), and two cervid strains (G8 and G10). 17,19,20 However, some of these distinct strains were originally defined many years ago as separate species or subspecies. Consequently, a taxonomic reappraisal relying mainly on mitochondrial data has proposed that E. granulosus species splits to four valid species including: 1) E. granulosus sensu stricto (G1-G3 complex), 2) E. equines (G4), 3) E. ortleppi (G5), and 4) E. canadensis (G6-G10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one of the main ancestral dispersion centers in the network analysis clustered identical haplotypes of G6 and G7 from China, Mexico, Peru, Sudan, and Russia. The species status of E. canadensis is still controversial, [1][2][3]5,25 because biologically different strains (G6-G10) have been unified. The camel (G6) and pig (G7) strains (both maintained primarily by dog-mediated domestic lifecycles from tropical to temperate zones) are ecologically and geographically segregated from G8 to G10 2,26 ; therefore, some works have suggested that G6 and G7 should be treated as a single species: E. intermedius.…”
Section: 5mentioning
confidence: 99%